In vitro and in vivo models of immunomodulatory activity of a hydroalcoholic fraction of Turnera ulmifolia Linn - Sruthi, Vuppula; Garige, Baba Shankar Rao (Rzeszów University Press, 2025)
Introduction and aim. The present study explores the immunomodulatory effects of the hydroalcoholic extract of Turnera ul mifolia through in vitro and in vivo models. Material and methods. The study examined cytotoxicity, cytokine production, and nitric oxide (NO) levels using RAW 264.7 murine macrophage cells, while in vivo assessments were performed using BALB/c mice. Results. In vitro, T. ulmifolia extract significantly increased cytokine levels and NO production in unstimulated cells while ef fectively inhibiting overproduction in LPS-stimulated cells, suggesting immunomodulatory and anti-inflammatory activities. In vivo experiments demonstrated that T. ulmifolia extract enhanced the immune response by improving macrophage phago cytic activity, increasing delayed-type hypersensitivity, increasing serum hemolysin levels, and enhancing thymus and spleen indices. These results highlight the potential of the T. ulmifolia extract as an immunomodulatory agent, regulating cytokine secretion and enhancing immune responses without causing cytotoxicity. Conclusion. The findings indicate promising therapeutic applications for T. ulmifolia extract in modulating immune function and inflammation.
Ethical approval for the study was obtained from Flair Labs, located at PLOT NO B 510, PALSANA, Surat-394315, Gujarat, India, under the registration number 1250/PO/RcBi/S/23/CPCSEA.
Keywords: hydroalcoholic; immunomodulatory activity; in vitro; in vivo; Turnera ulmifolia